2013
DOI: 10.1093/neuonc/not215
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput microRNA profiling of pediatric high-grade gliomas

Abstract: BackgroundHigh-grade gliomas (HGGs) account for 15% of all pediatric brain tumors and are a leading cause of cancer-related mortality and morbidity. Pediatric HGGs (pHGGs) are histologically indistinguishable from their counterpart in adulthood. However, recent investigations indicate that differences occur at the molecular level, thus suggesting that the molecular path to gliomagenesis in childhood is distinct from that of adults. MicroRNAs (miRNAs) have been identified as key molecules in gene expression reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 67 publications
3
51
0
Order By: Relevance
“…The role of miRNAs has been widely studied in multiple aspects of adult GBM biology, showing their profound involvement in the regulation of gene expression involving vital cellular processes such as angiogenesis, metabolic reprogramming and stem cell behavior . However, in this perspective, pediatric HGG is an understudied disease compared to their adult counterparts with only two studies on restricted number of miRNAs in pediatric HGGs . Here, we present, for the first time, genome‐wide miRNA as well as snoRNA expression signature in pediatric HGGs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The role of miRNAs has been widely studied in multiple aspects of adult GBM biology, showing their profound involvement in the regulation of gene expression involving vital cellular processes such as angiogenesis, metabolic reprogramming and stem cell behavior . However, in this perspective, pediatric HGG is an understudied disease compared to their adult counterparts with only two studies on restricted number of miRNAs in pediatric HGGs . Here, we present, for the first time, genome‐wide miRNA as well as snoRNA expression signature in pediatric HGGs.…”
Section: Discussionmentioning
confidence: 98%
“…It is potentially oncogenic in nature and regulates tumor development and maintenance. Miele et al . suggested that in pediatric HGGs, miR‐17/92 promotes cell proliferation through a possible quenching of tumor suppressor gene PTEN and activation of sonic hedgehog signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can occur via a perfect complimentary binding of the miRNA to the target mRNA (endonucleolytic cleavage of the mRNA) or by an imperfect complimentary binding to the target mRNA (translation repression). 32 Due to their cell cycle interference, miRNAs are involved either as oncogenes or as oncosuppressors in the pathogenesis of a huge variety of human cancers such as lung cancer, 33,34 prostate cancer, 35 colorectal cancer, 36,37 leukemia, [38][39][40] gliomas 41 and medulloblastoma, 42 diffuse large B-cell lymphoma, 43 hepatocellular carcinoma (HCC), 44 gastric cancer, 45,46 osteosarcoma, 47 renal cell carcinoma, 48 BC, 49 and OC. 50 Particularly, their presence in the blood has been shown to be associated with histology, clinical stage, survival, and oncogenic expression in OC and BC.…”
Section: Introductionmentioning
confidence: 99%